Effect of Dietary Zinc on Semen Quality of Cobb 500 Broiler Breeder Males - Amem, Mahmood H.M.; Al-Daraji , Hazim J. (International Journal of Poultry Science, 2011)
The purpose of the present research was to evaluate the effect of dietary supplementation with different levels of zinc (0, 50, 75, 100 mg/kg diet) on semen quality of Cobb500 broiler breeder males. The four experimental diets were as follows: T1 = the basal diet (control) without any addition (0 Zn). T2 = 50 mg Zn (pure zinc)/kg diet. T3 = 75 mg Zn (pure zinc)/kg diet T4 = 100 mg Zn (pure zinc)/kg diet. The results showed that, Zinc supplementation had significantly (p<0.05) increased spermatocrit, ejaculate volume, mass motility, individual motility, while dead, abnormal sperm percentage and acrosome deformities were depressed (p<0.05) as affected by zinc supplementation throughout study. As well as, dietary treatments influenced sperm concentration and ejaculate volume during the experimental long. Moreover, results also revealed the superiority (p<0.05) of dietary treatments as compared with control group in respect of total mean of all semen quality.